Understanding tourists' profile and preference of tourists' destination choice: A case study in Melaka World Heritage city - Ab Rahman, Syakir Amir; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (MIP, 2014)
Tourism sector is one of the world largest and fastest contributors to the economic sector. The recognition as UNESCO World Heritage City in 2008, has led to the city of Melaka to be the most visited city in Malaysia. There has been a great deal of research devoted to identify the tourist preferences in countries, regions, cities, and other areas. Such estimation is essential for producing comprehensive estimates of tourism economic benefits in an area. This paper presents an evaluation of tourists’ preferences among domestic and international tourists visiting Melaka. 1000 tourists were surveyed using diary records survey method. The result shows the purpose of heritage and conservation is the most important factors that motivate their visit to Melaka, while business purpose is the least motivating factors influencing the choice of destinations. It is also found that young, single and professional tourist is the new target market in Melaka.